Development of the climate change investigation (CCI) module to empowering sustainability literacy and global diversity in junior high school students - Contias Edar Buana; Muhammad Nurhudha; Kadek Dwi Hendratma Gunawan; Nurma Yunita Indriyanti; Riezky Maya Probosari; Lina Mahardiani (CV. FOUNDAE, 2025)
Background: Environmental issues are integral to science education, addressing the causes, impacts, and prevention of environmental damage. Investigative learning is essential to help students better understand these complex topics.Aim: This study aimed to determine the characteristics and feasibility of the Climate Change Investigation (CCI) module in empowering students’ sustainability literacy and global diversity.Method: The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection included expert validation and student-teacher response questionnaires.Results: The findings showed that the CCI module is an effective and engaging tool for enhancing students’ understanding of environmental issues and cultural awareness. The module also benefits teachers by introducing interactive, low-carbon, and sustainability-based learning media. Validation scores from material, media, and language experts confirmed its high feasibility. Student and teacher responses indicated a high level of satisfaction with the module's clarity, content, and relevance.Conclusion. The CCI module enables students to understand various causes and impacts of environmental degradation, recognize the regional variations in climate effects, appreciate the role of biodiversity, evaluate the influence of eco-friendly technologies, and participate actively in discussions. The module supports independent learning and contributes to shaping environmentally and culturally conscious students aligned with 21st-century educational goals.